Dampak Permainan Tradisional dan Kemampuan Motorik terhadap Keterampilan Lompat Jauh - Mudayat, Mudayat; Mualimin, Mualimin; Kuswoyo, Dilli Dwi (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of traditional games and motor skills on long jump skills of elementary school students in Metro, Lampung. This study used a quantitative descriptive method with a 2×2 factorial experimental design. The study population amounted to 103 students, with a sample of 24 male students selected using purposive sampling technique. Data were collected through motor tests that included agility, coordination, explosive power, and speed. Data analysis was carried out using normality, homogeneity, ANOVA, and hypothesis testing with the help of the SPSS for Windows version 20.0 application. The results showed that: (1) there are differences in long jump skills between students who take part in cricket games and those who take part in jump rope games; (2) there is an interaction between the type of traditional games and motor abilities on long jump skills; (3) there are differences in long jump skills between students with high motor abilities who take part in cricket games and jump rope; and (4) there are differences in long jump skills between students with low motor abilities who take part in cricket games and jump rope. It is concluded that traditional games have a significant influence on the long jump skills of elementary school students in Metro, Lampung.